CRITERIA AND INDICATORS OF INTELLECTUAL DEVELOPMENT «I» FUTURE ENGINEER - Tatyana Mayboroda (Вестник Северо-Кавказского федерального университета)
In article author's approach to determination of levels and structure intellectual «I» the identity of future engineer as subject of educational and future professional activity is considered. Author's definitions of definitions ((professionalism of the engineer», «personal and professional potential of the engineer» are considered. On the basis of the theoretical analysis and the pilot study conducted by the author of article external and internal integrated criteria, and also indicators of intellectual development «I» future engineer are deined, correlation dependences between them are established and interpreted.